2006
DOI: 10.1016/j.ipm.2005.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of multiple query reformulations on the web: The interactive information retrieval context

Abstract: This study examines the facets and patterns of multiple Web query reformulations with a focus on reformulation sequences. Based on IR interaction models, it was presumed that query reformulation is the product of the interaction between user and IR system. Query reformulation also reflects the interplay between the surface and deeper levels of user interaction. Query logs were collected from a Web search engine through the selection of search sessions in which users submitted six or more unique queries per ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
165
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(179 citation statements)
references
References 29 publications
12
165
0
2
Order By: Relevance
“…Ignoring the results for New, overall the most common query reformulation is Parallel (20.4%), Revision (18.9%), Specialization (17.6%), Back (12%) and Generalization (9%). The results are similar to previous findings where results showed that parallel is the most common form of reformulation and specializa- tions are performed more often than generalizations [2]. In this dataset we observe a high proportion of revision reformulations.…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…Ignoring the results for New, overall the most common query reformulation is Parallel (20.4%), Revision (18.9%), Specialization (17.6%), Back (12%) and Generalization (9%). The results are similar to previous findings where results showed that parallel is the most common form of reformulation and specializa- tions are performed more often than generalizations [2]. In this dataset we observe a high proportion of revision reformulations.…”
Section: Methodssupporting
confidence: 91%
“…Approaches to study reformulations are typically based on manually analyzing the transitions between query pairs in a session [2,6]. Alternatively, automatic techniques have also been used to learn types of query reformulation [5].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Belkin et al (2001), in a research entitled "Interactive exploration, design and evaluation of support for query reformulation in interactive information retrieval, report on the developed search tools for supporting interactive query reformulation in interactive (TREC) investigation task. Rieh and Xie (2006) in their research entitled "Analysis of Multiple query Reformulation on the Web: the interactive information retrieval context" stated that the purpose of their study was to explore various aspects and patterns of web query reformulation with an emphasis on query sequence. It was used to design search motor of the web and is the performances of an interactive reformulation tool.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In simple words, query reformulation is a process in which by the cooperation of the user and system, the revision and rearrangement of initial query is done manually so that the user can get to optimum results. In the interactional models of information retrieval, it is assumed that query reformulation is the product of interaction between a user and information retrieval system, which reflects the mutual effect between general and deep layers of a user's interaction (Rieh and Xie, 2006).…”
mentioning
confidence: 99%